Heterogeneity in Karakoram glacier surges - Quincey, Duncan J.; Glasser, Neil F.; Cook, Simon J.; Luckman, Adrian (Journal of Geophysical Research: Earth Surface, 2015)
Many Karakoram glaciers periodically undergo surges during which large volumes of ice and debris are rapidly transported downglacier, usually at a rate of 1-2 orders of magnitude greater than during quiescence. Here we identify eight recent surges in the region and map their surface velocities using cross-correlation feature tracking on optical satellite imagery. In total, we present 44 surface velocity data sets, which show that Karakoram surges are generally short-lived, lasting between 3 and 5 years in most cases, and have rapid buildup and relaxation phases, often lasting less than a year. Peak velocities of up to 2 km a -1 are reached during summer months, and the surges tend to diminish during winter months. Otherwise, they do not follow a clearly identifiable pattern. In two of the surges, the peak velocity travels down-ice through time as a wave, which we interpret as a surge front. Three other surges are characterized by high velocities that occur simultaneously across the entire glacier surface, and acceleration and deceleration are close to monotonic. There is also no consistent seasonal control on surge initiation or termination. We suggest that the differing styles of surge can be partly accounted for by individual glacier configurations and that while some characteristics of Karakoram surges are akin to thermally controlled surges elsewhere (e.g., Svalbard), the dominant surge mechanism remains unclear. We thus propose that these surges represent a spectrum of flow instabilities and the processes controlling their evolution may vary on a glacier by glacier basis. Key Points Karakoram glacier surges are heterogeneous in their character Karakoram surges do not conform to classic thermal and hydrological surge models Controls on surging may differ on an individual glacier basis